Application of Combined Dietary and Exercise Intervention in Pediatric Obesity and Its Impact on Anthropometric Measurements and Blood Lipid Parameters - Nie Y; Xiong F; Wang H; Yang F; Chen J (Journal of Multidisciplinary Healthcare)
Yang Nie,1 Fei Xiong,2 Hong Wang,3 Fengqiong Yang,1 Jianxin Chen1 1Children’s Health Department, Chongzhou Maternal and Child Health Hospital, Chongzhou, People’s Republic of China; 2Department of Child Health Care, West China Second Hospital, Sichuan University, Chengdu, People’s Republic of China; 3Child Health Care Department, Sichuan Maternal and Child Health Hospital, Chengdu, People’s Republic of ChinaCorrespondence: Fei Xiong, Email fazx841@163.comObjective: To evaluate the effects of a combined dietary and exercise intervention on anthropometric measurements and blood lipid profiles in obese children, and to provide evidence-based support for pediatric obesity management.Methods: This retrospective study included 130 obese children who underwent routine health examinations and interventions between January 2020 and October 2023. Participants were divided into two groups: the control group received health education only, while the observation group received additional dietary and exercise interventions. Pre- and post-intervention changes in anthropometric indicators, body fat levels, lipid profiles, inflammatory markers, physical activity levels, and parental satisfaction were assessed.Results: Baseline characteristics were similar between groups (P > 0.05). After intervention, the observation group showed significantly lower body weight, BMI, waist-to-hip ratio, body fat percentage, visceral fat area, and lipid levels (TG, TC, LDL-C), along with higher basal metabolic rate (P < 0.05). Physical activity increased and sedentary time decreased significantly in the observation group (P < 0.001). Additionally, inflammatory markers (IL-6, IL-8, TNF-α) were markedly reduced in the observation group (P < 0.05), and parental satisfaction was significantly higher compared to the control group.Conclusion: A combined dietary and exercise intervention significantly improves body composition, lipid metabolism, physical activity levels, and inflammatory status in obese children. This comprehensive model may be an effective, non-pharmacological strategy for promoting healthy growth and managing childhood obesity.Keywords: obese children, combined diet and exercise intervention, physical measurements, blood lipid levels